Multi-target mechanism of polyherbal extract to treat diabetic foot ulcer based on network pharmacology and molecular docking - Happy Elda Murdiana; Retno Murwanti; Nanang Fakhrudin; Zullies Ikawati (Shahrekord University of Medical Sciences, 2024)
Introduction: Diabetic foot ulcer (DFU) potentially leads to loss of function, infections, hospitalization, lower-extremity amputation, and even death. The potential therapeutic efficacy of a polyherbal candidate named TIP-Heal was identified for treating DFU. TIP-Heal, which stands for Tinospora crispa, Isotoma longiflora, and Piper betle L var nigra, consists of extracts from these three herbs in a ratio of 2:1:1. The Indonesian population commonly uses these herbs due to their wound-healing properties. It is our interest to analyse the mechanism of the polyherbal extract using network pharmacology and molecular docking. Methods: This study uses network pharmacology and molecular docking methods to analyze the multi-target mechanism of active compounds in TIP-Heal extract for DFU treatment. The proteins targeted by the bioactive chemical present in TIP-Heal and DFU were identified within a particular dataset with the keyword "homo sapiens." The identified target proteins were assessed using gene ontology (GO) analysis, the Kyoto Encyclopaedia of Gene and Genomes (KEGG) pathways, protein-protein interactions (PPIs), and molecular docking. Results: The critical proteins obtained were AKT serine/threonine kinase 1 (AKT1), caspase-3 (CASP3), epidermal growth factor receptor (EGFR), proto-oncogene tyrosine-protein kinase Src (SRC) and matrix metalloproteinase-9 (MMP-9). Several compounds, namely PubChem (Compound Identifier=CID: 5319898), 3-epiursolic acid, palmitic acid, and alpha-linolenic acid showed great potential as viable candidates to facilitate the healing process of DFU. Conclusion: The findings of this study indicate that the TIP-Heal extract has the potential to be used as a natural herbal treatment for DFUs with the involvement of AKT1, CASP3, EFGR, and SRC proteins.